EXPRESSION OF EPIDERMAL GROWTH FACTOR RECEPTOR IN SQUAMOUS CELL CARCINOMA OF THE HEAD AND NECK - KOIKE, SYUJI; SUZUKI, MAMORU; SATAKE, JUN-ICHI; MATSU-URA, KAZUTO; TAKASAKA, TOMONORI; OHI, KIYOYUKI (Nippon Jibi Inkoka Gakkai Kaiho, 1993)
Localization of epidermal growth factor receptor (EGFR) was investigated immunohistologically in 68 untreated patients with squamous cell carcinoma of the head and neck regions. These patients consisted of 16 with cancer of the lips and mouth, seven with mesopharyngeal cancer, six with epipharyngeal cancer, 15 with hypopharyngeal cancer, 10 with laryngeal cancer, 12 with maxillary cancer and two with other tumors (cancer of the auricle and cancer of the eyelid in one patient each). The patients consisted of 57 men and 11 women, with a mean age of 60 years. In cases with a normal oral mucosa, marked expression of EGFR was observed in the epithelial cell membrane, while expression decreased toward the luminal surface. Cancer cells also showed positive staining of EGFR in all patients, but the intensity of staining was inconsistent among them. Among the 32 patients in whom the staining intensity of EGFR was equal to or weaker than that in basal cells of the normal oral mucosa, 12 patients had lymph node metastasis. Twenty-eight of the 36 patients in whom the staining was stronger than that in the normal cells had lymph node metastasis, suggesting that overexpression of EGFR in carcinoma cells is a risk factor for lymph node metastasis of head and neck cancers (P<0.005). On the other hand, there were no obvious relationships between either the size or the degree of keratinization of the primary lesion and EGFR expression.